Personbetecknande verbavledningar i Ordbok över Finlands svenska folkmål. En utvärdering av ordbokens sökfunktioner - Sandström, Caroline; Åkerlund, Carola (Nordiske Studier i Leksikografi, 2018)
The study examines the various search possibilities in the e-dictionary Ordbok över Finlands svenska folkmål (Dictionary of Swedish Dialects in Finland) published in 2013. The dictionary project was initiated as early as in the middle of the 20th century, and the concrete editing process started in the 1960s; by 2007 four volumes of the dictionary had been published. To evaluate the search function we examine how a group of derivational suffixes, i.e. -are, -bla, -dra, -el, -er, -ing, -lla, -ska, -ssa, -us, are distributed in the e-dictionary, according to their geographical spread and semantic differences. Our results show that the search function developed for the dictionary is a helpful and efficient tool for finding patterns in the distribution of derivational suffixes, but for some purposes the search results need to be further analyzed manually.